(3TQM GdTeSjIs - (3GdMSf Hf eMeO Hf GdMSjf Gdbej GdfjSGHhQqj, fXGe GdOjf, hjbGd dg GdCYQL , GdpqfnXGe,J (B850 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdaQO HdG fO GdefRg Yf GdRhL hGdVO hHYO aEf CMhL Ndb Gddg Ydjg GdMSf Hf eMeO GdfjSGHhQi jbhd GdMSGH Yde dGjcGO jSJZfi Yfg WdGH GdYdhe hGdBOGH s
(3BNQgG (B:s
(3agPg bhGfjf EPG CJbfJ MaXgG edcJ ReGe ESJNQGL eWGdH TQjaI ai GdMSGH JeJ hGdMeO ddg s
(3cJH Ydi GdeNWhW GdTeSjI ai GdMSGH eY QSGdI GdcGajI ai GdMSGHs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B216 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B281s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B1062s
Keywords: (3GdQjGVjGJs